G463(P) Determining the health needs of children with special educational needs. (27th April 2015) - Miller, H; Juniper, T; Reid, P; Lloyd, C; Goodson, A; Rose, M
Abstract : Introduction: The goal of the SEND reforms is to improve the outcomes of children with special educational needs (SEN) and disabilities. One key strategy is to improve the coordination and integration of education, health and care services through joint commissioning. Commissioning can only be effective when services are designed around the needs of their services users. Little is known about the health needs of disabled children for whom the lack of data for planning purposes is the single biggest challenge to better outcomes. Aim: To describe the health problems and services use of children with SEN. To pilot an approach to data collection for services planning. A third objective, to assess the quality of medical reports, is reported separately. Method: We reviewed all the medical reports submitted between January and June 2014 for a Statement of Special Educational Needs (SSEN). Additional hospital statistics were collected. Results: Data were analysed on 125 children, 78% boys and 22% girls, median age 6.9 years (1.9–14.8). 65% of children were known to community paediatrics and 25% to CAMH services. 6% of children were LAC, 5% on CP plan, and 15% excluded from school. 39% children had autism, 7% ADHD, 26% SEMH, 9% physical needs, 8% sensory impairment (all types), 26% SLCN, 46% learning difficulties (all types), 8% SpLDs. 55% of the children had multiple needs, 6% were complex special needs. In the previous year 62% children attended hospital outpatients (1–16 visits), 10% of children were admitted to hospital (1–4 admissions) and 23% of children had been seen in A&E (1–7 visits). 50% of children were known to hospital specialities, 50% to S&L, 16% physiotherapy, 30% OT services. Many children had associated health problems (19% medical, 18% nutrition, 9% continence). Conclusions: Children with SEN have extensive health needs and are high users of health services. Our data is likely to be an underestimate as we only analysed hospital statistics and medical reports whose quality varied. SSEN reports provide important health data. Data collection and analysis from a broader range of services continues. The new Education, Health and Care process provides an opportunity for prospective data collection for services planning.